VACCINATION HESITATION FROM THE BIOETHICAL PERSPECTIVE: A CASE REPORT - Alt Parente, Elizabeth; Genovez Vieira Caetano, Carolina; Coppola Maciel Araújo, Flávia; Alvares Sathler, Gabriel; Gomes Andrade Vianna, Gabriela; Affonso Magalhães, Larissa; Fernanda Batista de Oliveira, Marayah; Godoy de Paula, Marina; Macedo Cardoso, Natália; Graça de Oliveira Mateus, Talita; Fernandes Lopes, Yasmin (Health and Society, 2024)
Introduction: Vaccine hesitation represents a significant challenge to public health, with serious consequences, such as the resurgence of eradicated diseases, the return of measles and pertussis in Brazil, as well as other immunoprevenable diseases, due to the fall in vaccination coverage. There is a bioethical conflict between the autonomy of parents who choose not to vaccinate their children and the lack of responsibility, as citizens, to protect public health. In addition, the responsibility of health professionals to work in accordance with the principles of beneficence and non-maleficence, so that they always indicate and encourage vaccines duly endorsed by science. Respect for autonomy should be balanced with the collective good, where vaccination hesitation contributes to the resurgence of preventable diseases and generates negative impacts on public health. Objective: Discuss vaccine hesitation from the perspective of bioethics from a real case report, addressing the repercussions of doctors’ instructions to their patients. Additionally, the legal aspects related to the obligation of vaccination in Brazil are discussed, with emphasis on collective protection and ethical duty to promote public health. METHOD: This is a descriptive and qualitative study based on a real case report of meningoencephalitis resulting from chickenpox, whose searches were performed in the Scielo, PubMed and Lilacs databases. Discussion: Varicella is a disease caused by the varicella-zoster virus, whose transmission occurs through respiratory aerosols or contact with the contents of skin lesions. Its main complications are meningoencephalitis, pneumonia, skin and ear infections. Meningoencephalitis is a rare interlocutory appeal that consists of acute central nervous system inflammation and can be fatal. Vaccination against chickenpox prevents injuries resulting from this infection. According to the legislation in force in the country, the obligation to immunize through a vaccine that, registered with a health surveillance body, is part of the National Immunization Program or its obligatory application determined by law is constitutional. Addressing the precepts of principalist bioethics, the present study relates them to the reported case, aiming to broadly discuss vaccine hesitation from medical advice. CONCLUSION: The case report highlights the importance of vaccination against the varicella zoster virus in preventing serious complications and the bioethical dilemma between parents’ autonomy and the responsibility of protecting the health of children and the community. Non -immunization, as in the case of the varicella, highlights the need to prioritize the principles of beneficence and non -maleficence. Although autonomy is essential, it should be balanced with the individual and collective good, especially in vaccination, where protection depends on adherence to immunization policies. Vaccine hesitation is a growing public health problem, requiring health professionals to be well formed to combat misinformation and promote evidence -based practices.